Cost of decentralized CAR T‐cell production in an academic nonprofit setting. Issue 12 (6th July 2020) - Ran, Tao; Eichmüller, Stefan B.; Schmidt, Patrick; Schlander, Michael
Abstract: Chimeric antigen receptor (CAR) T‐cell therapy is a promising immunotherapy with high acquisition costs, and it has raised concerns about affordability and sustainability in many countries. Furthermore, the current centralized production paradigm for the T cells is less than satisfactory. Therefore, several countries are exploring alternative T‐cell production modes. Our study is based on the T‐cell production experience in a nonprofit setting in Germany. We first identified the work steps and main activities in the production process. Then we determined the fixed costs and variable costs. Main cost components included personnel and technician salaries, expenditure on equipment, a clean room, as well as production materials. All costs were calculated in 2018 euros and converted into U.S. dollars. For a clean room with one machine for closed and automated manufacturing installed, annual fixed costs summed up to approximately €438 098 ($584 131). The variable cost per production was roughly €34 798 ($46 397). At the maximum capacity of one machine, total cost per product would be close to €60 000 ($78 849). As shown in the scenario analysis, if three machines were to be installed in the clean room, per production cost could be as low as €45 000 (roughly $59905). If a cheaper alternative to lentivirus was used, per production total cost could be further reduced to approximately €33 000 (roughly $44309). Decentralized T‐cell production might be a less costly and more efficient alternative to the current centralized production mode that requires a high acquisition cost. Abstract : What's new? Chimeric antigen receptor (CAR) T cell therapy is a promising therapeutic strategy for certain types of malignancies. However, high acquisition costs of commercial products, currently manufactured in a centralized mode, is controversial. Here, the authors examined the cost of an alternative method of T‐cell production in Germany. Based on maximum capacity of one machine for automated manufacturing, fixed costs were $584 131, with total cost per product about $78 849. With use of three machines or use of a less‐expensive viral vector, costs dropped significantly. The analyses suggest that decentralized CAR T‐cell production in a non‐profit setting would be relatively cost‐efficient.